2014
DOI: 10.1586/1744666x.2014.975211
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase Wip1 as a new therapeutic target for intestinal ischemia-reperfusion injury

Abstract: Intestinal ischemia/reperfusion (I/R) injury is a pathophysiology involving local tissue injury and organ dysfunction. Accumulating evidence has confirmed that the infiltration of neutrophils is of central importance in mediating intestinal I/R injury. On the other hand, adequate neutrophils in the intestine could also benefit the antibacterial translocation and tissue repair. Consequently, regulation of neutrophil immunity after intestinal I/R might be a promising therapy for controlling intestinal injury. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…They confirmed the previously obtained 9,37,39 data and showed that Wip1−/− mice produced more pro-inflammatory cytokines such as TNF- α , IL-6, IL-12 and IL-17 than WT mice. The elevation of these cytokine can be linked to the ability of Wip1 to regulate p53 and NF k B pathways.…”
Section: Wip1 In Regulation Of Immune Responsesupporting
confidence: 91%
“…They confirmed the previously obtained 9,37,39 data and showed that Wip1−/− mice produced more pro-inflammatory cytokines such as TNF- α , IL-6, IL-12 and IL-17 than WT mice. The elevation of these cytokine can be linked to the ability of Wip1 to regulate p53 and NF k B pathways.…”
Section: Wip1 In Regulation Of Immune Responsesupporting
confidence: 91%
“…We further demonstrated that Wip1 can modulate neutrophil function to regulate intestinal ischemia/reperfusion injury (26, 37) and inflammatory bowel diseases in a p38 MAPK-dependent manner (25). Moreover, Wip1 can also participate in neuro-inflammation through controlling tumor necrosis factor (TNF)-α synthesis (38) or NF-κB function (39).…”
Section: Wip1 In Inflammationmentioning
confidence: 84%
“…The downregulated expression of Wip1 was negatively related to the inflammatory cytokine production and bactericidal activities of neutrophils in a p38 MAPK-STAT1- and nuclear transcription factor (NF)-κB-dependent manner (24). Due to the importance of Wip1 in regulating neutrophil development and function, we also suggested that targets on Wip1 might be a new therapeutic strategy for the treatment of inflammatory bowel diseases (25) and intestinal ischemia reperfusion injury (26). …”
Section: The Role Of Wip1 In Immunitymentioning
confidence: 99%
“…Intestinal ischemia-reperfusion injury (IRI) is a potentially severe clinical syndrome of several major surgical procedures, including cardio-pulmonary bypass surgery, liver transplantation, bowel resection and transplantation, abdominal aortic aneurysm surgery, and strangulated hernias ( Yasuhara, 2005 ; Abboud et al, 2008 ; Nickkholgh et al, 2013 ). Intestinal IRI is a serial cascade of pathophysiologic changes of mucosal barrier failure, bacteria translocation, and inflammation caused by the disruption of blood and oxygen supply and the subsequent reperfusion of the intestine after arterial obstruction, venous thrombosis, and diffuse vasospasm ( Shen et al, 2014 ). The intestine is more sensitive to IRI, which damages the integrity of the intestinal mucosal barrier and may lead to bacterial translocation through the intestinal wall, peritonitis, and subsequent systemic inflammatory response syndrome (SIRS) ( Collard and Gelman, 2001 ; Cheng et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%